Effects of the processing parameter on the fibre length and physical properties of short glass reinforced TPNR composite / Syed Yusainee Syed Yahya - Syed Yahya, Syed Yusainee (Universiti Teknologi MARA, Pahang, 1998)
Blends of thermoplastic natural rubber (TPNR) reinforced composite with 10% volume fractions non directional short glass fibre were prepared by melt blending in a plasticorder mixer at various temperatures, times dan mixing rates. The optimum processing conditions were determined from the highest value of the tensile strength and was found that temperature was 135°C, mixing rate of 11 rpm and mixing time of II minutes. The tensile properties of the blend had decreased significantly with increasing amount of glass fibre. The SEM micrograph has shown that the distribution of fibre in the TPNR matrix was quite uniform.